The Impact of Clinical Pathway Application on The Quality and Quantity of Antibiotic Use in Inpatient Patients With Tyfoid Fever at Fmc Bogor Hospital - Gandes Winarni; Shirly Kumala; Hesty Utami R (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Typhoid fever is a global health problem, especially in developing countries, one of which is Indonesia. The incidence of resistance to the use of antibiotics in the treatment of typhoid fever can occur due to inappropriate use of antibiotics. This study aims to determine the impact of the application of clinical pathways on the quality and quantity of antibiotic use in typhoid therapy at FMC Bogor Hospital. This research is a descriptive analytic study conducted retrospectively which was analyzed using the Gyssens and ATC/DDD methods. The research data was taken from patient medical records for the period January-December 2018 and January-December 2020 which met the inclusion criteria. The results showed that from 115 medical records of typhoid fever patients, ceftriaxone was used as the most widely used antibiotic for typhoid therapy. The quality of antibiotic use as much as 40% was declared rational before the use of clinical pathways and as much as 57.3% after the use of clinical pathways (category 0), while the other 60% were irrational (categories I-VI) and after CP as much as 42.7% were included in category 0, the rest fall into the irrational category (Categories I-VI) which includes the use of antibiotics that are not appropriate for the administration interval, the use of antibiotics that are too long, the use of antibiotics that are too short, there are other antibiotics that are more effective, and there are other antibiotics that are less toxic /safer. The quantity of antibiotic use was stated to exceed WHO standards, namely the use of ceftriaxone by 81 DDD/100 patient days before the clinical pathway and 92.4 DDD/100 patient days after the clinical pathway. Based on the results of statistical tests, it was obtained 1) There were differences in the quality of antibiotic use between before and after the implementation of the clinical pathway in inpatients with typhoid fever at FMC Bogor Hospital; 2) There are differences in the quantity of antibiotic use between before and after the implementation of the clinical pathway in inpatients with typhoid fever at FMC Bogor Hospital. The results of this study are expected to be a consideration for the hospital as material for evaluation and improvement in order to increase the rationality of using antibiotics.